Comparative Clinical Trajectories Across Cannabis‐Related and Nonsubstance‐Related Psychoses - Mustonen, Antti; Niemelä, Solja; Denissoff, Alexander; Tanskanen, Antti; Mittendorfer‐Rutz, Ellenor; Lähteenvuo, Markku; Tiihonen, Jari; Taipale, Heidi (Wiley, 2026)
Background
Research indicates that first-episode psychosis (FEP) with cannabis use disorder (CUD) carries a substantial disease burden, but more granular clinical trajectories of cannabis-related psychoses remain unclear. This study examines the clinical trajectories of first clinically diagnosed FEP&CUD and cannabis-induced psychosis (CIP) in comparison with FEP without substance use disorder (SUD).
Methods
From the linkage of nationwide administrative and medical registers of Sweden (2006–2021), we identified 1772 individuals (84.1% men) with incident CIP, 1360 individuals (84.3% men) with FEP&CUD and matched individuals with FEP but without SUD and followed them up until 2023. We compared annual prevalence of psychiatric diagnoses before and after cohort entry, medication use, days in inpatient care, and the risks of hospitalization for psychosis and death.
Results
Mean age at first diagnosis was 26.6 years (SD 8.3) for incident CIP and 26.9 years (SD 8.4) for FEP&CUD and FEP without SUD. Individuals in the FEP without SUD cohort were more likely to have a record of schizophrenia diagnosis compared to the FEP&CUD and CIP cohorts during the first (14.41%, 6.25%, 2.37%) and second year (10.88%, 7.13%, 3.27%) after cohort entry. However, FEP&CUD and CIP cohorts had a more pronounced burden of inpatient treatment as well as elevated risks of hospitalization for psychosis (aHR = 1.66; 95% CI 1.49–1.86 and aHR = 1.47; 1.32–1.64) and death (aHR = 2.02; 1.44–2.82 and aHR = 1.80; 1.30–2.50) compared to individuals with FEP without SUD.
Conclusions
Cannabis-related psychoses, that is, FEP&CUD and CIP, were associated with poor outcomes, including high risk of hospitalization for psychosis and increased mortality, underscoring the need for targeted interventions. Moreover, the overlapping clinical trajectories suggest that cannabis-related psychoses may not represent clinically distinct entities but instead lie on a continuum.